Validation of reference genes for expression analysis in three Bupleurum species. Issue 1 (1st January 2019) - Yu, Ma; Liu, Dan; Li, Yu-Chan; Sui, Chun; Chen, Guang-Deng; Tang, Zhi-Kang; Yang, Cheng-Min; Hou, Da-Bin; Wei, Jian-He
Abstract: Radix Bupleuri (root of Bupleurum spp.) is an important medicinal herb. Its lateral root number is one of the decisive factors that influence the content of a major bioactive component, saikosaponin. To identify genes associated with content and total yield of saikosaponin, it is of key importance to select stable references in gene expression analyses using quantitative real-time polymerase chain reaction (qRT-PCR). In this study, 18 candidate reference genes were selected and evaluated through their expression stability during the lateral root development in tissue samples from B. chinense DC., B. falcatum L. and B. scorzonerifolium Willd. The GeNorm, NormFinder and Bestkeeper methods were used for selecting stably expressed internal controls in the three Bupleurum species. These results revealed that, among these 18 candidate reference genes, ADF7 showed the best performance in all the experimental systems. ADF5 and ADF1b could also be proposed as suitable reference genes for gene expression studies. This study supplied more candidate reference genes to monitor the content and yield of saikosaponin during lateral roots growth in the Bupleurum genus.